Senna alata (L.) Roxb. Ethnobotanical significance in Nepal - Sharma, Hari Devi; Gurung, Smriti; Lamichhane, Janardan (BMC Journal of Scientific Research, 2025)
Senna alata (L.) Roxb.is a well-recognized medicinal plant valued across the globe for its therapeutic properties which have been extensively utilized in traditional and modern herbal remedies. In Nepal like many other regions this plant holds significant ethno pharmacological importance, yet comprehensive documentation of its indigenous uses remains limited. This study aims to explore and document the traditional knowledge, applications and cultural significance of S. alata among different communities in Nepal providing insights into its role in indigenous healthcare practices and potential for further pharmacological research. The study was carried out in six districts of Nepal from March to November 2024. Semi-structured interviews were conducted in 6 districts involving 90 respondents. This research result showed that the species is primarily used for medicinal purposes (74.1%), with smaller proportions allocated to food (13.31%) and rituals applications (12.5%). The uses of the species varied in different communities of Nepal. Decoction (75.56%), paste (35.56%) and cooked (12.22%) were the forms mainly used by the local population. The leaves (81.11%) were the most commonly used part of the plant. Flowers (25.56%), seed (20%), stem (7.78%) and root (2.22%) were used, but to a lesser extent. In addition, leaves and flowers were mainly used parts of the species to treat skin related diseases while seeds and roots were used for constipation and fever. These results demonstrate the medicinal importance of S.alata in Nepal and suggest the need for priority actions for the sustainable management and use of the species. Further research on the medicinal components of different parts of the plant could aid its promotion and recognition.